Managerial Role of the Principal in the Implementation of School Digitalization at SMP Negeri 1 Kajen - Tejawati, Sari; Kusumaningsih, Widya; Soedjono, Soedjono (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Digital transformation in education demands not only technological adaptation but also strategic and visionary leadership. This study examines how the principal of SMP Negeri 1 Kajen implements key managerial functions planning, organizing, resource mobilization, and supervision in advancing school digitalization. Framed by transformational leadership theory and Kotter’s change management model, the analysis highlights leadership practices across stages of change. Using a qualitative phenomenological approach, data were collected through interviews, observations, and document analysis with triangulation to ensure credibility. Digitalization, defined as the integration of LMS, CBT, and the SIDIK application, was aligned with institutional goals through proactive planning. Organizational adjustments included team-based coordination and task delegation, while digital tools were supported by continuous teacher training. Although monitoring relied on reflective observation, it lacked systematic data use. Despite challenges such as limited digital competence and resistance to change, the principal employed inclusive strategies mentoring, collaboration, and phased implementation to build trust and capacity. The study concludes that effective digital leadership requires adaptive, inclusive, and reflective management to sustain and scale transformation.